First microbial-archaeocyathan boundstone record from early Cambrian erratic cobbles in glacial diamictite deposits of Namibia (Dwyka Group, Carboniferous). (3rd June 2019) - Perejón, A.; Rodríguez-Martínez, M.; Moreno-Eiris, E.; Menéndez, S.; Reitner, J.
Abstract : This study records the first occurrence of a lower Cambrian archaeocyathan fauna in limestone cobbles from Carboniferous glacigenic deposits of the Dwyka Group of the Aranos Basin in Namibia. Petrographic and microfacies analysis of 17 large, middle and standard thin sections reveals two distinctive limestone cobble facies: (a) bioclastic wackestone-packstone (hyoliths, trilobites, chancelloriids, crinoids and archaeocyaths); and (b) microbial-archaeocyathan boundstone dominated by calcimicrobes ( Epiphyton and Renalcis ), neomorphosed microbial crusts and crypto-fibrous calcite crusts around mainly regular archaeocyaths such as Polycoscinus scutatus, where encrusting ?sponges are accessory. The published stratigraphical and palaeocurrent data from the Dwyka Group, as well as published ages and the tectonothermal history of the underlying Nama Group, have been used in this study to establish the provenance of these lower Cambrian cobbles. The archaeocyaths from the Aranos Basin are: Favilynthus contractus, Ajacicyathus aequitriens, Kisasacyathus subacutus, Plicocyathus sp., Erismacoscinus endutus, Erismacoscinus ganigobisensis sp. nov., Erismacoscinus cf. stephensoni, Polycoscinus scutatus, Chabakovicyathus sp., Loculicyathidae gen. et sp. indet., Dictyocyathus aranosensis sp. nov., Graphoscyphia sp., Archaeopharetra irregularis and Syringocnema favus . The presence of Syringocnema favus and other species allows us to determine a precise upper Stage 3 or early-mid Botoman age for the erratic cobbles of the Dwyka Group from the Aranos Basin. The Namibian fauna reported here provides a key record in Cambrian palaeobiogeography based on archaeocyathan assemblages. The archaeocyath faunal assemblage from the Dwyka cobbles is diverse and has an analogous richness to allochthonous assemblages from Permo-Carboniferous glacigenic deposits of other localities in south-western Gondwana. Thus, the archaeocyath-bearing cobbles from the Dwyka Group of Namibia could provide a better understanding of the different palaeo-ice flow direction models of the Permo-Carboniferous glacial deposits in future palaeogeographical reconstructions of south-western Gondwana. http://zoobank.org/urn:lsid:zoobank.org:pub:0365EE4C-D7FA-4C09-89DF-27C9E1F55511